Physicochemical, pharmacokinetic, efficacy and toxicity profiling of a potential nitrofuranyl methyl piperazine derivative IIIM-MCD-211 for oral tuberculosis therapy via in-silico–in-vitro–in-vivo approach. (February 2018) - Magotra, Asmita; Sharma, Anjna; Singh, Samsher; Ojha, Probir Kumar; Kumar, Sunil; Bokolia, Naveen; Wazir, Priya; Sharma, Shweta; Khan, Inshad Ali; Singh, Parvinder Pal; Vishwakarma, Ram A.; Singh, Gurdarshan; et al.
Abstract: Recent tuberculosis (TB) drug discovery programme involve continuous pursuit for new chemical entity (NCE) which can be not only effective against both susceptible and resistant strains of Mycobacterium tuberculosis (Mtb) but also safe and faster acting with the target, thereby shortening the prolonged TB treatments. We have identified a potential nitrofuranyl methyl piperazine derivative, IIIM-MCD-211 as new antitubercular agent with minimum inhibitory concentration (MIC) value of 0.0072 μM against H37Rv strain. Objective of the present study is to investigate physicochemical, pharmacokinetic, efficacy and toxicity profile using in-silico, in-vitro and in-vivo model in comprehensive manner to assess the likelihood of developing IIIM-MCD-211 as a clinical candidate. Results of computational prediction reveal that compound does not violate Lipinski's, Veber's and Jorgensen's rule linked with drug like properties and oral bioavailability. Experimentally, IIIM-MCD-211 exhibits excellent lipophilicity that is optimal for oral administration. IIIM-MCD-211 displays evidence of P-glycoprotein (P-gp) induction but no inhibition ability in rhodamine cell exclusion assay. IIIM-MCD-211 shows high permeability and plasma protein binding based on parallel artificial membrane permeability assay (PAMPA) and rapid equilibrium dialysis (RED) assay model, respectively. IIIM-MCD-211 has adequate metabolic stability in rat liver microsomes (RLM) and favourable pharmacokinetics with admirable correlation during dose escalation study in Swiss mice. IIIM-MCD-211 has capability to appear into highly perfusable tissues. IIIM-MCD-211 is able to actively prevent progression of TB infection in chronic infection mice model. IIIM-MCD-211 shows no substantial cytotoxicity in HepG2 cell line. In acute toxicity study, significant increase of total white blood cell (WBC) count in treatment group as compared to control group is observed. Overall, amenable preclinical data make IIIM-MCD-211 ideal candidate for further development of oral anti-TB agent.